LEGAL PROTECTION FOR NEW CREDITORS IN THE IMPLEMENTION OF CREDIT TAKEOVER WITH MORTGAGE GUARANTEE - Pujiyono, Pujiyono; Toha, Syarief (Yustisia, 2017)
This research aimed to identify and analyze legal protection for new creditors in the takeover of credit with mortgage guarantee. Type of Research is a normative legal research or an equation with doctrinal research. The results of this research shows that the implementation of the credit take over with collateral mortgage starting from the loan application by the debtor and all the completeness of the terms of credit application, to do a survey to customers. If it is eligible, then continuing to make a credit proposal in which will be submitted to a credit comitee. If it is approved then continued with the credit agreement and collateral agreement that are required to bring the debtor. Then the bank employees accompany the debt to the former creditor, to make payment with funds obtained from third party to make payment with funds obtained from third party. If the repayment has been done, required to request full payment slip and genuine proof of guarantee ownership, then they can be burden by mortgage, roya has to be done first. The transfer mechanism of mortgage in credit takeover is too risky for a new creditor if the Roya’s mail can not be published on the same day. So that way is provide less certainty and legal protection for the new creditors.